2012
DOI: 10.1007/s13197-012-0646-7
|View full text |Cite
|
Sign up to set email alerts
|

Quality and shelf life of cooked buffalo tripe rolls at refrigerated storage under vacuum packaging condition

Abstract: Cooked buffalo tripe rolls prepared from a combination of buffalo tripe and buffalo meat by using mincing and blade tenderization process were stored at 4 ± 1 °C in polyethylene teraphthalate laminated with polythene (PET/PE) pouches under vacuum packaging condition. The samples were evaluated for physico-chemical parameters, microbial quality and sensory attributes at regular intervals of 0, 7, 14, 21 and 28 days of storage. Significant changes were seen in physico-chemical, microbial and sensory characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
2
1
0
Order By: Relevance
“…El-Nashi et al (2015) also recorded a significant ( p < 0.05) decrease in the moisture content of beef sausages incorporated with pomegranate peel powder during storage. Similar observations were reported by Anandh et al (2014), who also observed a significant decrease in moisture content of buffalo tripe rolls under refrigerated storage.…”
Section: Resultssupporting
confidence: 90%
“…El-Nashi et al (2015) also recorded a significant ( p < 0.05) decrease in the moisture content of beef sausages incorporated with pomegranate peel powder during storage. Similar observations were reported by Anandh et al (2014), who also observed a significant decrease in moisture content of buffalo tripe rolls under refrigerated storage.…”
Section: Resultssupporting
confidence: 90%
“…The decrease in the moisture content of the products with storage may be attributed to the evaporative losses. Similar observations were reported by Anandh et al (2014) who also observed a significant decrease in moisture content of vacuum packaged buffalo tripe rolls under refrigerated storage. Kim et al (2014) also recorded a significant decline in the moisture content of vacuum packaged dry cured pork.…”
Section: Resultssupporting
confidence: 90%
“…The results obtained in the study in respect of TBARS values (mg malanoldehyde [MDA]/Kg) revealed a progressive increase (p≤0.01) in all the treatment groups (Table-3) throughout the study period of 15 days ranging from 0.11 to 0.33 mg MDA/Kg. However, significantly lower (p≤0.01) levels of thiobarbituric acid reactive substance (TBARS) values were recorded in the treated sausages which might be due to the antioxidative effect of various phenolic compounds present in conventional and LS [2,3] and also due to vacuum packaging of sausage samples [25]. At the end of the storage periods, the TBARS values of all the sausage samples were recorded to be well within the permissible limits of 1-2 mg MDA/Kg [26].…”
Section: Resultsmentioning
confidence: 99%